POSITIONING PARIWISATA SYARIAH STUDI KASUS PADA HOTEL SOFYAN SYARIAH - Tamitha Intassar Husen; Nabila Hilmy Zhafira (universitas teuku umar, 2019)
Associated with the new government program announced in October 2013, Sharia Tourism. This study was conducted to analyze how much the tourism industry can flourish once sharia determine appropriate marketing development for Hotel Sofyan Betawi, which became one of the pioneers of sharia tourism in Indonesia. Since 1996 Sofyan Betawi Hotel had changed the concept of conventional management into the management of sharia. Although since 1996, the company's revenue management implementations always up and said to be quite good, but until now stand, consumers of Hotel Sofyan Betawi is not yet fully know that the hotel management company under the auspices of sharia management. In addition, many consumers and communities who do not understand the meaning and essence of sharia in its application to business and management that is often misinterpreted.The preparation of the marketing plan, aims to continue the growth of existing products and develop the marketing area of sharia products provided by the company, came to the fore a clear targetKeywords: Tourism Sharia, Sharia Hotel, Business Sharia, Sharia Marketing, Marketing Plan, Environmental Analysis.